Research on the Road Methodology and Practice of Studying Traffic, Driving Habits, and Sustainable Mobility - Bezjak, Simona; Podjed, Dan (ZRC SAZU, Založba ZRC, 2017)
How do people drive on roads and behave in traffic? How can we change driving habits and encourage more environmentally responsible modes of transportation? These are the two main questions to which the volume tries to answer. It tackles the problems of driving, traffic, transportation, and mobility fully, rather than from a single perspective, which has tended to be the norm so far. The authors describe how we can weave together qualitative and quantitative approaches, how useful interviews are for understanding driving comfort, the power ethnography has to help us understand the lifestyle of drivers, which technological tools and approaches are the most useful for analyzing styles of driving, how to explore vehicles and traffic by analyzing language, how traffic might improve or worsen our way of life from a psychological point of view, and how we can encourage environmentally friendly behavior and practices on both the road and in life in general.